The use of reading comprehension strategies and its interaction with grade point average among second-year English majored students at Mekong University : - Lâm, Thái Quang (Can Tho University, 2009)
The present study aims to find out: The frequency use of reading comprehension strategies of second-year English majored students, the most frequently used reading comprehension strategies, the interaction between reading strategy use and students' Grade Point Average.